Great Whole Grain Breads - Ojakangas, Beatrice (Book collections on Project MUSE., 2002)
"Possibly the best such bread book on the market . . . every recipe a winner." Jane BrodyWith more than 250 sweet-and-savory recipes, easy-to-follow, step-by-step techniques for mixing and kneading, and special hints for working with whole grains, Great Whole Grain Breads should find a place in every baker's kitchen.